Access to bank credit and firm innovation in Egypt: New evidence from the World Bank enterprise survey - Ayoub Saadi; Mariem Liouaeddine; Hanan Amin Mohamed (Sustainable Futures)
This study examines the impact of bank credit access on innovation among Egyptian firms, using data from 3,025 companies in the World Bank's 2020 Enterprise Survey. Employing logistic regression and propensity score matching, the study assesses how access to credit influences various types of innovation, including R&D investment, acquisition of intellectual property, and new product creation. Results show that firms with bank credit are 67 % more likely to innovate, with a significant positive effect on R&D activities and intellectual property acquisition. Additionally, propensity score matching confirms a 5 % higher likelihood of innovation for firms with credit access, supporting the robustness of these findings. However, company size and sales volume are associated with decreased innovation likelihood, indicating constraints faced by larger firms and those with high sales. Competitive market conditions further enhance new product development probability by 42 %. Overall, the study highlights the crucial role of bank credit in fostering firm innovation in Egypt.